A Universal New Definition of Heart Failure With Improved Ejection Fraction for Patients With Coronary Artery Disease - Huang, Haozhang; Liu, Jin; Lei, Min; Yang, Zhou; Bao, Kunming; Li, Qiang; Lai, Wenguang; Wang, Bo; He, Yibo; Chen, Shiqun; Ou, Chun-Quan; Abudukerimu, Maimaitiaili; et al. (Frontiers in Physiology, 2021)
Aims: The aims of this study were to describe the characteristics and outcomes of the universal new definition of heart failure with improved ejection fraction (HFimpEF) and to identify predictors for HFimpEF among patients with coronary artery disease (CAD). Methods: CAD subjects with heart failure with reduced ejection fraction (HFrEF) (EF ≤ 40%) at baseline were enrolled from the real-world registry of the Cardiorenal ImprovemeNt study from January 2007 to December 2018. The new definition of HFimpEF was defined as left ventricular EF (LVEF) of≤40% at baseline and with improvement of up to 40% and at least a ≥ 10% increase during 1 month to 1 year after discharge. Results: Of the 747 CAD patients with HFrEF (86.7% males, mean age: 61.4 ± 11 years), 267 (35.7%) patients conformed to the new HFimpEF definition. Patients with HFimpEF were younger (adjusted odds ratio [aOR]: 0.98 [0.97–0.99]) and had a higher rate of hypertension (aOR:1.43 [1.04–1.98]), lower rate of percutaneous coronary intervention (PCI) treatment at the time of detection of HFrEF (aOR: 0.48 [0.34–0.69]), history of PCI (aOR: 0.51 [0.28–0.88]), history of acute myocardial infarction (aOR: 0.40 [0.21–0.70]), and lower left ventricular end diastolic diameter (aOR: 0.92 [0.90–0.95]). During 3.3-year follow-up, patients with HFimpEF demonstrated lower rates of long-term all-cause mortality (13.1% vs. 20.8%, aHR: 0.61[0.41–0.90]). Conclusion: In our study, CAD patients with HFimpEF achieved a better prognosis compared to those with persistent HFrEF. Patients with CAD meeting the criteria for the universal definition of HFimpEF tended to be younger, presented fewer clinical comorbidities, and had lower left ventricular end diastolic diameter.